Discipleship in a Multireligious World: living the Jesus Way and loving within the Trinity’s embrace - Clarke, Satianathan (Uniting Church studies, 2025)
This essay has two parts. The first section briefly evaluates two unhelpful theological models and then suggests how the Trinity can be creatively utilized as a Christian template for working out a spacious yet faithful theology of religions. The second section focuses on a pragmatic question: What would Christian discipleship look like in our multireligious world when we commit to generous compassion for all God’s communities with a singular passion for Christ? The balance between spacious universality in the Triune One and God’s particularity in Jesus Christ offers a productive means to passionately proclaim the Christian gospel while compassionately engaging with neighbours from other religions. The essay concludes by arguing that Christian discipleship in an interreligious world can be reimagined by uniting Christian embassy and interfaith hospitality.